In the infant's mind's ear: evidence for implicit naming in 18-month-olds. - Mani, N; Plunkett, K (2010)
Do infants implicitly name visually fixated objects whose names are known, and does this information influence their preference for looking at other objects? We presented 18-month-old infants with a picture-based phonological priming task and examined their recognition of named targets in primed (e.g., dog-door) and unrelated (e.g., dog-boat) trials. Infants showed better recognition of the target object in primed than in unrelated trials across three measures. As the prime image was never explicitly named during the experiment, the only explanation for the systematic influence of the prime image on target recognition is that infants, like adults, can implicitly name visually fixated images and that these implicitly generated names can prime infants' subsequent responses in a paired visual-object spoken-word-recognition task.